2019
DOI: 10.1101/656538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enriched G-quadruplexes on the Drosophila Male X Chromosome Function as Insulators of Dosage Compensation Complex

Abstract: The evolution of sex chromosomes has resulted in half X chromosome dosage in males as females. Dosage compensation, or the two-fold upregulation in males, was thus evolved to balance the gene expression between sexes. However, the step-wise evolutionary trajectory of dosage compensation during Y chromosome degeneration is still unclear. Here, we show that the specific structured elements G-quadruplexes (G4s) are enriched on the X chromosome in Drosophila melanogaster.Meanwhile, on the X chromosome, the G4s are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Sixteen papers reported either outbreak investigations or contact tracing studies reporting transmission from an index case during the pre-symptomatic period [ 13 , 19 , 21 , 26 , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ] ( Table 2 ). Of those, eleven studies were included in the quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen papers reported either outbreak investigations or contact tracing studies reporting transmission from an index case during the pre-symptomatic period [ 13 , 19 , 21 , 26 , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ] ( Table 2 ). Of those, eleven studies were included in the quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, having meals together, or playing cards with the index case were exposure activities associated with transmission. The remaining one study reported an outbreak in a restaurant [ 40 ] and four studies exclusively reported family cluster outbreaks [ 30 , 32 , 33 , 39 ]; these investigations did not test contacts outside the household, and it is challenging to truly differentiate transmission during the pre-symptomatic period from symptomatic transmission in the household setting ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%